Health Belief Model Theory Application on Voluntary Counseling and Testing among Homosexual Men in Bandung Greater Area - Argya Nareswara; Chrysanti Murad; Irvan Afriandi (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: The number of human immunodeficiency virus (HIV) cases is high and is constantly increasing. Homosexual men as a transmission niche is not only significant in terms of numbers, but also in natural aspects of anal sex, tropism of HIV-1, and high-risk behavior. Voluntary Counseling and Testing (VCT) is important for accelerating diagnosis and management plan; yet the uptake on high-risk population in Indonesia is low. A behavior-reasoning theory, Health Belief Model (HBM), attempts to explain whether or not individuals engage in certain health behavior. This study tries to assess participation rate of VCT, to portray HBM variables perception, and to depict significance of HBM variables towards VCT uptake or VCT intention. Methods: This study was conducted in October-November 2014 using cross-sectional design; 127 respondents were gathered according to Respondent Driven Snowball Sampling. This study used an internet-based questionnaire derived from Champion’s 1984 mammogram HBM questionnaire. Privacy and compensation were obtained. The Chi square test and logistic regression of HBM variables were done. Results: The VCT uptake was low (15.7%). Certain sexual experience and commitment were significant (Commitment to Men p=0.027, Oral Sex experience with men p=0.001, Anal Sex Experience with men p=0.038). Chi Square test revealed significance on Perceived Susceptibility, Perceived Benefit, and Cues to Action. Conclusions: Uptake of VCT is considerably low compared with total high risk population and other similar studies. Personal Susceptibility to HIV/AIDS is recommended to be emphasized; while VCT Benefit and Cues to Action in young homosexual men communities are better encouraged. [AMJ.2016;3(4):595–604]DOI: 10.15850/amj.v3n4.945